2019
DOI: 10.1186/s13002-019-0341-0
|View full text |Cite
|
Sign up to set email alerts
|

Where tulips and crocuses are popular food snacks: Kurdish traditional foraging reveals traces of mobile pastoralism in Southern Iraqi Kurdistan

Abstract: BackgroundIraqi Kurdistan is a special hotspot for bio-cultural diversity and for investigating patterns of traditional wild food plant foraging, considering that this area was the home of the first Neolithic communities and has been, over millennia, a crossroad of different civilizations and cultures. The aim of this ethnobotanical field study was to cross-culturally compare the wild food plants traditionally gathered by Kurdish Muslims and those gathered by the ancient Kurdish Kakai (Yarsan) religious group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…In food ethnobotanies, raw snack consumption primarily emerges during the adoption of mobile pastoralism, which local communities might have co-evolved. Our findings are in line with previous ethnobotanical studies that frequently reported snacks as the dominant food category [19,20,[52][53][54]. The most commonly quoted wild vegetables were Allium spp., Amaranthus viridis, Lepidium draba, Portulaca quadrifida, Polygonatum verticillatum, Rumex dentatus, Urtica dioica and an unidentified taxon, and these wild vegetables have been frequently reported in the Pakistani food ethnobotanical literature [18][19][20][42][43][44][45][46][47][48].…”
Section: Wild Food Plant Usessupporting
confidence: 92%
“…In food ethnobotanies, raw snack consumption primarily emerges during the adoption of mobile pastoralism, which local communities might have co-evolved. Our findings are in line with previous ethnobotanical studies that frequently reported snacks as the dominant food category [19,20,[52][53][54]. The most commonly quoted wild vegetables were Allium spp., Amaranthus viridis, Lepidium draba, Portulaca quadrifida, Polygonatum verticillatum, Rumex dentatus, Urtica dioica and an unidentified taxon, and these wild vegetables have been frequently reported in the Pakistani food ethnobotanical literature [18][19][20][42][43][44][45][46][47][48].…”
Section: Wild Food Plant Usessupporting
confidence: 92%
“…Some important wild food plants ( Figure 4 ) and dishes prepared by the visited communities were available for photographing ( Figure 5 ). Traditional culinary processing included cooking the plants as vegetables (43 mentions), followed by raw snacks (33), confirming what documented in other ethnobotanical studies too [ 73 , 74 , 75 ]. Raw snacks were eaten especially by transhumant herders, and it has been shown that herding develops specific linkages between humans and their surrounding ecosystem [ 76 , 77 , 78 , 79 ].…”
Section: Resultssupporting
confidence: 76%
“…Indeed, in Sardinia, cardu are gathered, often with the help of a knife (due to their thorniness), peeled with the blade, and consumed on the spot, possibly as a way to pass the time while grazing sheep, but ultimately, their crunchiness provides a pleasant chewing experience. Indeed, the texture of the plant may have contributed to the shaping of food preferences in the pastoralist context [22]. In addition, cardu stems or tubers are often watery and may have been used as thirst quenchers, especially in late spring and the beginning of summer when the plants are more turgescent.…”
Section: Cardu: a Key Emic Plant Group In The Pastoral Cultural Heritage Of The Mediterraneanmentioning
confidence: 99%
“…Indeed, pastoralism is often related to specific categories of plants. For example, in Iraq, Kurdish pastoralists were found to consume more snacks than the neighboring more horticulturalist-driven Kakei [22] and much more than Assyrians [23]. Even more specifically, Volpato and Di Nardo [24] explored the pivotal relation between the Sahrawi camel nomads and a specific savannah plant in Western Sahara.…”
Section: Introductionmentioning
confidence: 99%